Assessment of Hypertension-Mediated Organ Damage - OTT, Christian; Schmieder, Roland (Elsevier, 2023)
The individual impact of arterial hypertension on several hypertension-mediated organ damages (HMODs) varies widely. This chapter mainly addresses HMODs with arterial hypertension being the most important attributable risk factor. HMOD can be detected in an early subclinical (asymptomatic) stage, but once HMOD, even intermediate, has developed, these conditions are by far overwriting any risk prediction from the cardiovascular (CV) risk factor scores. Hence, the specific impact of HMOD is particular in (younger and middle-aged) patients with a probable reclassification of their individual risk estimation. A variety of techniques are available nowadays to diagnose HMOD of the brain, heart, eyes, kidneys, and vasculature in different organs, but with differences in sensitivity and specificity as well as applicability is limited depending on the availability of the various techniques and the reimbursement strategy of the national health care systems. The clinical importance of HMOD is also underlined by the fact that regression of HMOD is clinically a useful tool for evaluation of the efficacy of (more aggressive and immediate) antihypertensive treatment in individual patients. Therefore this chapter also emphasizes the consequences of HMOD regression by antihypertensive treatment, and attempts to establish whether or not changes of HMOD have related prognostic significance.
CRIS-Team Scopus Importer:2023-11-24
Keywords: blood pressure; brain; eye; heart; hypertension-mediated organ damage (HMOD); kidney; vasculature